Dynamic motion analysis of snowboard turns by the measurement of motion and reaction force from snow surface - Hirose, K.; Doki, H.; Kondo, A. (Procedia Engineering, 2012)
This paper deals with the dynamic motion analysis of snowboard turns by the measurement of motion and reaction force from snow surface. The motion measurement system measures 3-axis angular velocity, 3-axis acceleration and 3-axis magnetic field. The measurement system of reaction force measures 3-axis force vector and 3-axis moment vector about reaction force from snow surface. The measurement experiment was conducted by the snowboarder attaching the measurement systems. The motion measurement systems were attached to body segments of the snowboarder, and the measurement system of reaction force was installed between the binding and the snowboard. In this experiment, the snowboarder conducted carving turn. The 3D posture was estimated by applying the sensor fusion. The joint torque (lumber vertebra, hip, knee, and ankle) was calculated from the 3D posture, the angular velocity, the angular acceleration, the acceleration, and the reaction force from snow surface by applying inverse dynamics. The dynamic motion analysis of snowboard turns using the joint torque was carried out. The results of the motion analysis indicated the major features of snowboard turns. The proposed method and the analytical results can be used to skill rating, the development of equipments and the improvement of training method for snowboarding.